A numerical and experimental investigation of non-linear deformation behaviours in light-frame timber walls. (1st February 2022) - Kuai, Le; Ormarsson, Sigurdur; Vessby, Johan; Maharjan, Rajan
Abstract: In recent decades, there is a trend in Scandinavian countries to build multi-storey residential houses using prefabricated timber modules. It is a highly efficient construction process with less environmental impact and less material waste. A significant building element in the timber modules is the light-frame timber wall, which has to be carefully analysed and optimized in this process. This paper presents a new parametric Finite Element (FE) model that can simulate both in-plane and out-of-plane deformations in the light-frame walls. A new and flexible (Eurocode based) approach to define the properties of the mechanical connections is introduced. A numerical model is presented through simulations of several walls that were verified with full-scale experiments. The results indicate that the numerical model could achieve fairly reasonable accuracy with the new approach. Furthermore, several parametric studies are presented and discussed from global and local points of view, to investigate the effects of certain parameters that are not considered in the design method according to Eurocode 5.